PEREMPUAN LEMBUT YANG PERKASA KANDUNGAN IDEOLOGI DALAM NOVEL PEREMPUAN KEUMALA - Parapat, Nelson Halong (Istek Widuri Jakarta, 2016)
This paper presents that in the portrayal of real life, engaging media to produce ideologies and the entiretext of any category whether news media or drama or feature, advertising and other content that producesan ideology. Regularly media presents an overview of the world by making assumptions about the world thatthey represent. Likewise the novels as a form of media from various media in the society.Epic novel Perempuan Keumala written by Endang Moerdopo, assumed to contain a charge of ideologyfrom the writer. Therefore, this paper will describe the picture of the ideology in question, which is notexplicitly but only implied in the story of the courage and heroism of a woman, Keumalahayati, gentle andcharming.As a result of the analysis, it was concluded that it needs to be studied more in depth again is whetherideology in the novel Perempuan Keumala this really is an ideology which can be categorized as pureideology of women. These critical questions arise, because the prevailing culture in the society is a culturethat is the product of a man's world. Even the meaning of the symbols used in the community about womencame from and created by men, who incidentally was also used by the women in representing ideas or theirideas about the equality of women. This critical musings also as a starting point in the search furtherreconstruction ideology completely pure of, by and for women.